Cable health degradation IV - Ching, Chee Yong (Nanyang Technological University, 2022)
Throughout this project, I aim to study the cable’s conduction loss and its impact on the insulation, by focusing specifically on the tan δ as an indication of the cable insulation’s health. To carry out the tan δ test, first I’ll measure the polarized current of the cable. From the polarized current, I can reverse calculate the relevant values for the equivalent RC circuit parameters. These RC parameters can be used to calculate the tan δ using equations from PDC method.